2020
DOI: 10.46328/ijonse.36
|View full text |Cite
|
Sign up to set email alerts
|

Technology in the Teaching of Mathematics: An Analysis of Teachers’ Attitudes during the COVID-19 Pandemic

Abstract: One of the most significant events of the 21st century is the birth of modern technologies, specifically the development of electronic digital computers. Much more with the emergence of the new normal education, this technology's impact on science and business is very rampant. It is already affecting the educational enterprise in significant ways. Thus, the researcher conducted a study on teachers’ attitudes toward using technology in mathematics teaching the COVID-19 pandemic. The researcher used the descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 14 publications
2
37
0
9
Order By: Relevance
“…-Remote teaching‖ has become a worldwide phenomenon due to COVID-19, resulting in a temporary shift to online teaching (Ananga, 2020;Angelova, 2020;Atabey, 2021;Bradley, 2021;Cakin & Kulekci Akyavuz, 2021;ElSaheli-Elhage, 2021;Hodges at al., 2020;Ilhan, G. O., Kaba & Sin, 2021;Marpa, 2021;Paudel, 2021;Serhan, 2019;Unger & Meiran, 2020). These exceptional circumstances have brought the use of technology in education to the attention of a broader university public.…”
Section: Introductionmentioning
confidence: 99%
“…-Remote teaching‖ has become a worldwide phenomenon due to COVID-19, resulting in a temporary shift to online teaching (Ananga, 2020;Angelova, 2020;Atabey, 2021;Bradley, 2021;Cakin & Kulekci Akyavuz, 2021;ElSaheli-Elhage, 2021;Hodges at al., 2020;Ilhan, G. O., Kaba & Sin, 2021;Marpa, 2021;Paudel, 2021;Serhan, 2019;Unger & Meiran, 2020). These exceptional circumstances have brought the use of technology in education to the attention of a broader university public.…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus-2019 epidemic has damaged not only physical health, but also the psychological health and resilience of individuals. In a highly interconnected and globalized world, the social and economic effects of the epidemic have recently become evident (Ananga, 2020;Atabey, 2021;Atilgan & Tukel, 2021;Batmang et al, 2021;Cakin & Kulekci Akyavuz, 2021;ElSaheli-Elhage, 2021;Hebebci, Bertiz, & Alan, 2020;Marpa, 2021;McKibbin, 2020;Nnebedum, Obuegbe,& Nwafor, 2021;Tümen Akyıldız, 2020). The management of workrelated factors affecting mental health in a pandemic scenario appears to be crucial to support people's participation into social life and thus psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the effectiveness of using technology in online learning. Students like the rich technological resources and easy accessibility of information offered by the Internet to inspire them to study mathematics (Marpa, 2020). Innovative solutions leveraging technology can help bridge the education gap during uncertain circumstances such as the current pandemic (Chick et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%